2017
DOI: 10.1111/ggi.13053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water bath temperature on physiological parameters and subjective sensation in older people

Abstract: These results suggest that hot water bathing during cold seasons might induce more serious physiological changes in older people. Geriatr Gerontol Int 2017; 17: 2164-2170.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Evidence shows that IAP is associated with poor physical health. Prior researchers have identified IAP as the most important environmental risk factor globally associated with adverse health effects [36,37,38,39,40,41,42,43,44,45,46,47,48]. However, there is little empirical evidence of the relationship between IAP and depression based on nationally representative data, especially in developing countries [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that IAP is associated with poor physical health. Prior researchers have identified IAP as the most important environmental risk factor globally associated with adverse health effects [36,37,38,39,40,41,42,43,44,45,46,47,48]. However, there is little empirical evidence of the relationship between IAP and depression based on nationally representative data, especially in developing countries [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical pilot trial conducted in Germany showed that hypothermic baths (HTB) do have generalized efficacy in depressed patients. The results of a non-controlled HTB study aimed at 20 depressive patients, also conducted in Germany, showed an improvement after hypothermic baths [46,47]. Furthermore, HTB, especially before bedtime, improved sleep quality in healthy, insomniac people and elderly patients with depression and vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly participants did not feel that 41 °C was hot. During the 15-minute bath, body temperature did not increase as much in elderly participants compared to that in young participants, and elderly participants are reported to have low sensitivity to warm temperatures (Ono et al 2017, Taylor et al 1995. The temperature at which the elderly feels comfortable bathing, the young find unpleasant (Taylor et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, it is important to determine why the bathing time increases in elderly persons. Previous studies have reported a smaller increase in the body temperature of elderly participants during bathing compared to that in young participants (Takahashi et al 2007) and elderly individuals have a decreased sensation of changes in temperature (Ono et al 2017). For these reasons, the bathing time of an elderly person tends to be longer.…”
Section: Introductionmentioning
confidence: 94%
“…The elderly regularly attend the thermal environment for various indications and the physiological and psychological effects of the treatments are quantified. To respond to the urgent request of healthy ageing for all nations [7], the influence of therapeutic programmes is also questioned on global and specific health perceptions [8,9]. Although biomedical and public health outcomes are necessary, they are insufficient for comprehensive outcome assessment.…”
Section: Introductionmentioning
confidence: 99%